(untitled) (Jurnal Riset Agribisnis dan Peternakan, 2025)
The quality of the goat meat sold needs to be considered for food safety for consumers. The purpose of this study is to find out the physical quality and hedonic quality of goat meat from the beginning of selling to the end of selling while being sold in a traditional market in Purworejo. The samples in this study were obtained from all markets that sell goat meat as many as two vendors at the Pagi Plaza market, as many as two traders at the Baledono market, and as many as two traders at the Kutoarjo market. Based on the results of the physical quality test of goat meat from the beginning of selling to the end of selling while being sold in the traditional market in Purworejo, including pH, moisture content, water binding, and cooking shrinkage are still at normal levels. Based on the results of the study, the pH of goat meat at Pasar Pagi Plaza is 7.25 which means that the pH of goat meat at traders in Pasar Plaza is not good, the pH level in the goat meat sold. The results of the analysis of the hedonic test of goat meat from the beginning of selling to the end of selling while being sold at the traditional market in Purworejo in terms of aroma and color have no difference between traders and the time of sale except for the texture. As for the texture of the meat, there is a difference in texture in goat meat, the opening hours are better than the end hours between traders and the sales time.